The German Constitutional Court's PSPP Judgment: Impediment and Impetus for the Democratization of Europe. Issue 5 (July 2020) - Feichtner, Isabel
Abstract: The article explores the understandings of democracy underlying the judgment and its implications for the democratization of Europe. I read the judgement, critically, as impediment and, constructively, as impetus for the democratization of money and society. Firstly, I recount how the Federal Constitutional Court (FCC) through the construction of a "right to democracy" and the concepts of "ultra vires act" and "integration responsibility" asserted its jurisdiction over the limits of European integration. The court's reasoning prompts me to understand the judgment not as a defense of democracy, but rather as an instance of upholding a "rule of law" that impedes the democratization of society. Secondly, I turn to the pronouncements on the demarcation of monetary from economic competences by the Court of Justice of the European Union (CJEU) and the FCC. I explain what I hold to be the weaknesses in the FCC's critique of the CJEU from a doctrinal perspective. I then propose to read the PSPP judgment constructively as introducing a procedural requirement that may democratize monetary policy. Thirdly, I situate my reading of the judgment in the larger debate on the democratization of society and, more specifically, money.